The Sammohavinodanī-Atthayojanā: Translation and Analytical Study - Upachai, Thanawut (Mahachula Academic Journal, 2026)
This qualitative research article aims to: (1) examine the historical background and structural composition of the Sammohavinodanī Atthayojanā; (2) translate the Sammohavinodanī Atthayojanā from Pāli into Thai; and (3) analyze its doctrinal principles and intrinsic values. The study employed a documentary research method, with data analyzed according to the stated objectives and presented descriptively. The findings reveal that the Sammohavinodanī Atthayojanā is an exegetical text elaborating on the Sammohavinodanī Aṭṭhakathā of the Abhidhamma Piṭaka. It was composed by Venerable Ñāṇakitti Thera of Lanna during the reign of King Tilokarāj, around the 21st Buddhist century. The primary purpose of this work is to expand upon and elucidate Abhidhamma doctrines in a manner that is both systematic and accessible to learners. The text encompasses the eighteen analytical divisions (vibhaṅga) of the Abhidhamma, namely: aggregates (khandha), sense bases (āyatana), elements (dhātu), truths (sacca), faculties (indriya), dependent origination (paṭiccasamuppāda), foundations of mindfulness (satipaṭṭhāna), right efforts (sammappadhāna), bases of success (iddhipāda), factors of enlightenment (bojjhaṅga), the Noble Path (magga), meditative absorptions (jhāna), immeasurable states (appamaññā), disciplinary rules (sikkhāpada), discriminations (paṭisambhidā), knowledges (ñāṇa), minor topics (khuddakavatthu), and the heart of the Dhamma (dhammadhaya). Collectively, these sections delineate the structure of the mind, the processes of phenomena, and the progressive path toward the cessation of suffering. The research further introduces the MDI Model, a conceptual framework derived from the study, which represents the essential pedagogical and practical values found in the Sammohavinodanī Atthayojanā. This model comprises three interrelated dimensions of spiritual learning: (1) the dispelling of misunderstanding, (2) the cultivation of insight and cognitive skill, and (3) the integration of Dhamma into daily life. Through this triadic process, learners can internalize Abhidhamma teachings as transformative knowledge applicable to contemporary living.